THE RELATIONSHIP OF RIVER WATER USE BEHAVIOR WITH THE OCCURENCE OF DIARROW DISEASES IN GAMPONG DAH, RUNDING DISTRICT, SUBULUSSALAM CITY IN 2017 - Tumangger, Lia Cinta Afrida; Fajriansyah; ferdi riansyah, ferdi riansyah (Aceh Sanitation Journal, 2022)
The background A river is a form of the aquatic ecosystem which has an important role in the hydrological cycle. decrease in river quality if the water can not be used accoerding to the water river quality. The utilization of river water has decreased its quality due to contamination causing health problems as diarrhea. The purpose of this study is to know the relationship between the dhearea of river water use on the of occurence diarrheal diseases in Gampong Dah Subdistrict Runding Subulussalam.This research is analytic descriptive with a crossectional design with 65 samples and the sampling technique is done by Random Sampling. The study was conducted from 12 to 16 June 2017 in Gampong Dah subdistrict Runding Subulusalam city. Data analysis was done by chi-square statistical test (x2).The result of this research shows that there is a correlation between knowledge, attitude, and action with diarrhea disease in Gampong Dah Subdistrict Runding Subulussalam with p <0,05.The result of data analysis by using the Chi-square test proved that knowledge, attitude, and action relate to diarrhea disease in Gampong Dah Sub Runding Subulussalam. With p-value for knowledge is 0,017, attitude with p-value 0,044 and action with p-value 0,026. It is expected that communities should limit the use of river water to meet daily needs such as brushing, bathing, and cooking and switch to using dug well water as a source of clean water to meet daily needs.